The effectiveness of color values ​​in perceiving movement In women's fabric designs (Journal of the College of Basic Education, 2022)
Women's fabrics are considered to be design structures that require the existence of vocabulary that serves as an aesthetic and self-expression, and the first of these vocabulary is color and its ability to cause kinetic action on the surface of the cloth. This stems from the ability of color to find color variables and gradations that add to the cloth a kinetic sequence in the transition between design elements. Hence, color is one of the important elements in the design of women's picnic fabrics, based on its influences, which start from compositional and end aesthetically, allowing the designer to find factors affecting the recipient's psyche through the kinetic dimension caused by color.